Nicaragua : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
This country brief provides an overview of tobacco control legislation, use, and taxation in the country. This country brief provides an overview of tobacco control legislation, use, and taxation in the country. Nicaragua became a Party to the WHO Framework Convention on Tobacco Control in 2008 and was the first country in the world which ratified the FCTC Protocol to Eliminate Illicit Trade in Tobacco Products. Data on smoking prevalence and tobacco consumption in Nicaragua are scarce, and it is difficult to estimate recent tobacco consumption trends among adults. However, the decline in the prevalence of current smoking among GYTS participating adolescents from 20.4 percent in 2003 to 13.8 percent in 2014 among boys and from 12.8 percent in 2003 to 10.3 percent in 2014 among girls may be considered an indicator of tobacco control policy success. In 2009, Nicaragua switched from ad valorem to specific excise system for cigarettes. The specific excise tax rates and cigarette prices increased in 2012-2016. Available data demonstrate some decline in cigarette sales in Nicaragua in 2013-2017, as cigarettes became less affordable after the price increase and the taxation policy was beneficial for public health. Specific excise rates in 2017 and 2018 were increased by only 5 percent annually, and it was insufficient both for the reduction of tobacco affordability and for the increase of the government revenue. In February 2019, Nicaragua adopted rather substantial cigarette excise hikes: by 210 percent in 2019 and further by 25 percent in 2020 and 38 percent in 2021. These tax hikes are able to reduce tobacco consumption in the country and bring additional resources to the government coffers. However, the tobacco industry will probably try to distort positive results of the taxation reform. The government should be ready to counteract these tactics using the experience of other countries and conducting careful and timely monitoring of indicators of cigarette prices, supply, and sales. Tobacco use surveillance and monitoring should be developed in Nicaragua, including a regular collection of information on smoking prevalence, tobacco consumption and various economic indicators.